A novel hypothesis for histone-to-protamine transition in Bos taurus spermatozoa. Issue 3 (March 2017) - Sillaste, Gerly; Kaplinski, Lauris; Meier, Riho; Jaakma, Ülle; Eriste, Elo; Salumets, Andres
Abstract : DNA compaction with protamines in sperm is essential for successful fertilization. However, a portion of sperm chromatin remains less tightly packed with histones, which genomic location and function remain unclear. We extracted and sequenced histone-associated DNA from sperm of nine ejaculates from three bulls. We found that the fraction of retained histones varied between samples, but the variance was similar between samples from the same and different individuals. The most conserved regions showed similar abundance across all samples, whereas in other regions, their presence correlated with the size of histone fraction. This may refer to gradual histone–protamine transition, where easily accessible genomic regions, followed by the less accessible regions are first substituted by protamines. Our results confirm those from previous studies that histones remain in repetitive genome elements, such as centromeres, and added new findings of histones in rRNA and SRP RNA gene clusters and indicated histone enrichment in some spermatogenesis-associated genes, but not in genes of early embryonic development. Our functional analysis revealed significant overrepresentation of cGMP-dependent protein kinase G (cGMP-PKG) pathway genes among histone-enriched genes. This pathway is known for its importance in pre-fertilization sperm events. In summary, a novel hypothesis for gradual histone-to-protamine transition in sperm maturation was proposed. We believe that histones may contribute structural information into early embryo by epigenetically modifying centromeric chromatin and other types of repetitive DNA. We also suggest that sperm histones are retained in genes needed for sperm development, maturation and fertilization, as these genes are transcriptionally active shortly prior to histone-to-protamine transition.